The Red Harmful Plague in Times of Climate Change: Blooms of the Cyanobacterium Planktothrix rubescens Triggered by Stratification Dynamics and Irradiance - Knapp, Deborah; Fernández Castro, Bieito; Marty, Daniel; Loher, Eugen; Köster, Oliver; Wüest, Alfred; Posch, Thomas (Frontiers in Microbiology, 2021)
Planktothrix rubescens is a harmful planktonic cyanobacterium, forming concentrated metalimnetic populations in deep oligo- and mesotrophic lakes, even after successful restoration. In Lake Zurich (Switzerland), P. rubescens emerged as a keystone species with annual mass developments since the 1970s. Its success was partly attributed to effects of lake warming, such as changes in thermal stratification and seasonal deep mixing. However, recent observations based on a biweekly monitoring campaign (2009 to 2020) revealed two massive breakdowns and striking seasonal oscillations of the population. Here, we disentangle positive from negative consequences of secular lake warming and annual variations in weather conditions on P. rubescens dynamics: (i) Despite the high survival rates of overwintering populations (up to 25%) during three consecutive winters (2014 to 2016) of incomplete deep convective mixing, cyanobacterial regrowth during the following stratified season was moderate and not overshooting a distinct standing stock threshold. Moreover, we recorded a negative trend for annual population maxima and total population size, pointing to a potential nutrient limitation after a series of incomplete winter mixing. Thus, the predication of steadily increasing blooms of P. rubescens could not be confirmed for the last decade. (ii) The seasonal reestablishment of P. rubescens was strongly coupled with a timely formation of a stable metalimnion structure, where the first positive net growth in the following productive summer season was observed. The trigger for the vertical positioning of filaments within the metalimnion was irradiance and not maximal water column stability. Repetitive disruptions of the vernal metalimnion owing to unstable weather conditions, as in spring 2019, went in parallel with a massive breakdown of the standing stock and marginal regrowth during thermal stratification. (iii) Driven by light intensity, P. rubescens was entrained into the turbulent epilimnion in autumn, followed by a second peak in population growth. Thus, the typical bimodal growth pattern was still intact during the last decade. Our long-term study highlights the finely tuned interplay between climate-induced changes and variability of thermal stratification dynamics and physiological traits of P. rubescens, determining its survival in a mesotrophic temperate lake.